Pemetaan Potensi Glamour Camping (Glamping) Di Kawasan Destinasi Pariwisata Di Lombok - Yoyok Antoni Antoni; Dimas Purnama Dewata (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
The purpose of the research is to determine the mapping of Glamping potential in Tourism Destinations in Lombok. The type of research conducted is descriptive qualitative research, by analyzing the results of in-depth interviews and focus group discussions (FGD) which are carried out interactively and participatory with informants in the research. Informants in the research from tourism industry players, policy makers in local and regional governments, especially in the research object area, namely Glamping tourism destinations in the Lombok tourism destination area. The results of the study on mapping the potential of glamping in tourism destinations in Lombok, as follows the potential for glamping development in tourism destinations, especially in the tourist villages of Sedau, Bilebante, Kembang Kuning and Sembalun can be done by considering: First, location, including the existence of the location, access and view. Second, activities and activities in it, namely camping, other tourism, provision of facilities and rates. fees charged to tourists Third, facilities and arrangements, namely places of worship, public facilities, glamping locations, public camping locations and supporting culinary delights that provide comfort and security for tourists. Fifth, the actors or managers, can be done independently, individuals/business entities, Bumdes, Pokdarwis and others.